The lifestyle of Tuyuhun royal descendants: Identification and chemical analysis of buried plants in the Chashancun cemetery, northwest China - Lu, Yongxiu; Liu, Bingbing; Liu, Ruiliang; Jiang, Hongen; Yang, Yishi; Ye, Qinhan; Li, Ruo; Wei, Wenyu; Chen, Guoke; Dong, Guanghui (Frontiers in Plant Science, 2022)
The Tuyuhun Kingdom (AD 313-663) was one of the most famous regimes in northwest China during the early medieval period. However, the lifestyle and spiritual pursuit of their descendants who became allied with the Tang Dynasty remains enigmatic. The excavation of the Chashancun cemetery, a Tuyuhun royal descendant (AD 691) cemetery in the Qilian Mountains in northwest China, reveals a large amount of uncharred plant remains. These remains provided a rare opportunity to explore the geographical origin of the buried crops and their social implications. In total, 253,647 crops and 12,071 weeds were identified. Foxtail millet and broomcorn millet represent 61.99% and 30.83% of the total plant remains, with the rest being barley, buckwheat, beans and hemp. The oxygen isotope and trace elements of the crop and weed suggest that broomcorn millet, foxtail millet, barley, buckwheat, and hemp were sourced from different regions. The assemblage of plant remains in the Chashancun cemetery suggests millet cultivation played an important role in the livelihoods of Tuyuhun descendants, and the location of the elite Tuyuhun cemetery and multi-sources of different buried crops may reflect their memory of ancestors and homelands. This case study provides a unique perspective to understand the interactions among human subsistence strategy, geopolitical patterns and local natural environments in northwest China during the late 7th Century.